Review of genitourinary tuberculosis with focus on end-stage renal disease - Lima, Neiberg A. (2012)
Tuberculosis (TB) is a current public health problem, remaining the most common worldwide cause of mortality from infectious disease. Recent studies indicate that genitourinary TB is the third most common form of extra-pulmonary disease. The diagnosis of renal TB can be hypothesized in a non-specific bacterial cystitis associated with a therapeutic failure or a urinalysis with a persistent leukocyturia in the absence of bacteriuria. We report on the case of a 33-year-old man who presented on admission end stage renal disease (ESRD) secondary to renal TB and a past history of pulmonary TB with important radiologic findings. The diagnosis was based on clinical findings despite all cultures being negative. Empiric treatment with tuberculostatic drugs was started and the patient became stable. He was discharged with no symptom, but without renal function recovery. He is on maintenance hemodialysis three times a week. TB is an important cause of kidney disease and can lead to irreversible renal function loss.